Role of Computed Tomographic Enterography for Evaluation of Small Bowel Diseases - Sahu , Niranjan; Chaudhury , Maheswar; Siddheshwar , Kapse Pratik (Advanced Concepts in Medicine and Medical Research Vol. 2, 2023)
The goal is to assess 2% mannitol's potential for optimum small bowel distension and the Computed Tomographic Enterography (CTE) characteristics of different small bowel illnesses. Diagnostic imaging and in particular cross-sectional modalities (US, CT, and MR) have a critical and complementary role in diagnosis and management of small bowel diseases. Radiologists should be aware of advantages and disadvantages of each imaging test in order to choose the best option, considering the specific small bowel disease and the patient’s characteristics (age, gender, clinical status). In this cross-sectional investigation, 105 people with small intestinal illnesses were included. This research comprised patients between the ages of 10 and 85 who complained of fever, stomach discomfort, nausea, vomiting, abnormal bowel habits, loss of appetite, and weight loss. To compare the diagnosis with the available histological and ultrasonographic findings, CTE pictures were evaluated. The majority of the research participants displayed signs of CTE, including symmetrical wall thickening (53.3%), peri-bowel inflammatory alterations (61%), mucosal hyperenhancement (39%), and mural stratification, or the target sign (33.3%). Ileocecal tuberculosis (11.5%), small intestinal inflammation (7.6%), and Crohn's disease (6.7%) made up the bulk of CTE diagnoses. Other conditions include small bowel neoplastic masses, diverticula, ischemic bowel disease, strictures, and intussusception. CTE has the vital role of first-line modality in the work-up of suspected small intestinal diseases and helps evaluate disease activity before endoscopy, particularly in inaccessible segments. It allows a better depiction of extra-enteric complications of the bowel.